Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Kebijakan Dividen (Studi Empiris pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Fitriana, Susi; Alamsyah, Alamsyah (Postgraduate, University of Mataram, 2024)
This study aims to analyze the effect of profitability, liquidity, and company size on dividend policy. This research is descriptive research using a quantitative approach. The data collection process was carried out using documentation techniques. The population in this study were all food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2020-2022, totaling 84 companies. By using purposive sampling technique, 17 sample companies were obtained. In this study, dividends are measured using FCF, ROE, and CR. The panel data analysis method used in this research is multiple linear regression analysis using Eviews version 12. The research findings show that ROE has a negative and significant effect on DPR. And CR has a positive and significant effect on DPR. Meanwhile, LN has a negative and insignificant effect on DPR.